How the Republic of Korea's Financial Structure Affects the Volatility of Four Asset Prices - Hong G. Min; Park, Jong-goo (World Bank, Washington, DC, 2015)
The authors explore how Koreas financial structure affects the volatility of asset prices. Documented empirical evidence of the relationship between financial structure and financial crisis, sheds light on the relationship between asset price volatility - extreme variations in price - and financial structure. And the volatility of financial and non-financial asset prices provides an indirect link between an economys financial structure and the likelihood of financial crisis. Using time-series data on a se of indicators measuring financial structure, the authors examine how Koreas financial structure affects the volatility of the real effective exchange rate, the money market rate, government bond yields, and stock prices. They find: 1) There is a stable long-term relationship between financial structure and volatility in the real effective exchange rate, the money market rate, stock prices, and the yield on government housing bonds. 2) Financial structure affects asset price variables asymmetrically. Some variables volatility increases, and others diminish, suggesting that monetary policies should target different asset markets to achieve different goals. If the goal of the monetary authority is to stabilize the money market rate, for example, intervening in the banking sector is more efficient than intervening in other financial sub-sectors. 3) The higher volatility of stock prices reflects the thin stock market in Korea. 4) The stability of the yield on government housing bonds reflects the Korean governments policy of stabilizing the nations housing supply by isolating the housing market from the impact of Koreas financial structure. 5) Restrictions on foreigners ownership of domestic stock in Korea during the period analyzed, and the fact that most capital flows through commercial banks, affect the exchange rate, which is determined (at least in the short run) by capital flows in the foreign exchange market.